Killing our Spirituality: The Basel Missionaries and the Bakossi Man in Muetug, Cameroon - Ndille, Roland Ntongwe (The international journal of religion and spirituality in society, 2015)
Several studies in the history of Christianity in Africa have described instances where the granting of permission for European missionaries to operate on native soils was on the condition of non-interference in native traditional worship. Co-existence between traditionalists and Christians was apparently the modus vivendi. But, the rare case of a whole community called Mwetug being induced by the Basel Missionaries to completely destroy their traditional forms and symbols of worship in their conversion to Christianity is the story that this paper seeks to bring to lime light. Popular opinion in the area continues to appreciate the coming of missionaries to Mwetug but highly regrets their orientalist approach to evangelization for ‘killing’ traditional Mwetug Spirituality. Unfortunately, the missionaries in their literature have hardly taken responsibility for the destruction of the secret societies; giving the impression that it was the natives’ self-motivated desire to demonstrate their faith in Christianity. While putting the missionaries and their local prelate at the core of the events, the paper attempts a critique of this approach to evangelism and uses the conflict between tradition and Christianity at that time and the subsequent calls for the re-instatement of the abolished native spiritual essence as apparent weaknesses in that approach to the evangelization of Africa. It concludes that a symbiotic interaction between Bakossi Spirituality and Christianity heralded in some evangelizing principles such as acculturation would have been the best practice; principles which emanated from a more objective evaluation of the Bakossi society which the missionaries had failed to carryout. In terms of methodology, we have made use of historical research tools tapping extensively from "the oral sources that we still have before it is too late," archival materials as well as some other empirical sources.